2017
DOI: 10.1021/acs.analchem.7b03528
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Metabolite-Related DNA Oxidation and Adduct Damage from Aryl Amines Using a Microfluidic ECL Array

Abstract: Damage to DNA from the metabolites of drugs and pollutants constitutes a major human toxicity pathway known as genotoxicity. Metabolites can react with metal ions and NADPH to oxidize DNA or participate in SN2 reactions to form covalently linked adducts with DNA bases. Guanines are the main DNA oxidation sites, and 8-oxo-7,8-dihydro-2-deoxyguanosine (8-oxodG) is the initial product. Here we describe a novel electrochemiluminescent (ECL) microwell array that produces metabolites from test compounds and measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…In our previous work using a similar methodology to form metabolites from test chemicals using CYPs and microsomes, we found that rates of DNA adduction and oxidation correlated very well with Comet DNA damage assays and rodent TD 50 genotoxicity assays, as did the reactivities of CYPs and microsomes. In the present work, we are only substituting proteins for DNA, so we expect the reactivities of CYPs and microsomes to also correlate with natural systems. We previously showed that CYPs and supersomes provide the same or better activity and the same selectivity when on magnetic beads compared to dispersed in solutions. …”
Section: Discussionsupporting
confidence: 53%
“…In our previous work using a similar methodology to form metabolites from test chemicals using CYPs and microsomes, we found that rates of DNA adduction and oxidation correlated very well with Comet DNA damage assays and rodent TD 50 genotoxicity assays, as did the reactivities of CYPs and microsomes. In the present work, we are only substituting proteins for DNA, so we expect the reactivities of CYPs and microsomes to also correlate with natural systems. We previously showed that CYPs and supersomes provide the same or better activity and the same selectivity when on magnetic beads compared to dispersed in solutions. …”
Section: Discussionsupporting
confidence: 53%
“…Electrochemiluminescence (ECL) is light emission from excited state luminophores generated by electrochemical reactions, which possesses better spatiotemporal control in comparison with chemiluminescence ( Richter, 2004 ; Hu and Xu, 2010 ; Hesari and Ding, 2017 ; Liu et al, 2019 ). Because no external light illumination is required to generate ECL emission, ECL has unique advantages, such as low background and high sensitivity, et al It has manifested itself to be a powerful transduction signal for the determination of small biomolecules, DNA and protein biomarkers in biosensing and clinical diagnostics ( Doeven et al, 2014 ; Wu et al, 2014 ; Lim et al, 2016 ; Bist et al, 2017 ; Ji et al, 2017 ; Yang et al, 2018 ; Zhou et al, 2018 ; Zhang et al, 2019a ; Jones et al, 2020 ). Moreover, ECL has recently emerged as a useful surface analysis technology because of its intrinsic surface-confined and surface-sensitive nature ( Guo et al, 2017 ; Zhang et al, 2019b ; Zanut et al, 2019 ; Ma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ECL has been used for immunoassay and ultrasensitive detection of a wide range of analytes in different fields like medical diagnostics, environmental analysis, and (bio)sensors fabrication [4–8] . The subsequent implementation of ECL principles in microscopy allowed new frontiers and new applications in particular for multiplexing analysis, [9, 10, 11] making the investigation of the ECL mechanisms possible at nanoscale level, especially for sensor application and for biological characterizations. For these reasons, ECL microscopy is a very promising technique for the surface‐confined mapping and quantification of several extremely diluted analytes [12–19] …”
Section: Figurementioning
confidence: 99%